If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2x + 12 = 35 + -4x + -9 Reorder the terms: 12 + 5x + -2x = 35 + -4x + -9 Combine like terms: 5x + -2x = 3x 12 + 3x = 35 + -4x + -9 Reorder the terms: 12 + 3x = 35 + -9 + -4x Combine like terms: 35 + -9 = 26 12 + 3x = 26 + -4x Solving 12 + 3x = 26 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 12 + 3x + 4x = 26 + -4x + 4x Combine like terms: 3x + 4x = 7x 12 + 7x = 26 + -4x + 4x Combine like terms: -4x + 4x = 0 12 + 7x = 26 + 0 12 + 7x = 26 Add '-12' to each side of the equation. 12 + -12 + 7x = 26 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 26 + -12 7x = 26 + -12 Combine like terms: 26 + -12 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| y=-(1+1)(1-3) | | 2g-8=10-4g | | X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 | | 10r-12=-28 |